Factors influencing performance and gross profitability in grazing beef cattle under tropical conditions - Dominguez-Castaño, Pablo (2022)
The aim of this study was to evaluate the effect of sex, average daily gain (ADG) and purchase size on performance and gross monthly profitability (GMR) and to know the structure of association between economic and performance variables in grazing cattle located under rainy tropical conditions in Colombia. The records of 598 cattle from the years 2016 to 2021 were analysed. The animals were classified by sex and into three groups based on the live weight (small, medium, and large) when purchased. The least squares methodology was used to determine the influence of the effects and their interaction on the GMR (p<0.05). The final model included the factors of sex, size and their interaction while ADG and days to fattening (DF) were included as linear covariates within the model. The principal component analysis methodology was used to discover the association structure between variables. Females produced higher GMR and gained less weight than males (7.7 and 6.7% and 399±8.0 and 526±5.6 g, respectively). Small animals generate higher GMR (8.4±0.1%), than medium (6.9±0.1%) and large (6.2±0.2%). Principal component analysis grouped five features into two principal components (PC), retaining 76.8% of the total variance. The (CP1) grouped the variables initial weight and DF. CP2 was strongly associated with final weight, ADG, and GMR. The effect of sex, ADG and size influenced the GMR. Principal components analysis was efficient in identifying associations between the characteristics studied, where initial weight and DF present an inversely proportional association, and final weight, ADG and GMR have a directly proportional association.